Adult Foot and Ankle Trauma at Schroeder Mounds (11He177): A Late Woodland Period Site in Illinois - (:unkn) unknown (My University, 2020)
Foot and ankle trauma in adults may be accidental or caused by physical activities that increase the likelihood of injury. Little is known about the organization of labor or health of the presumed forager-farmers of the later Late Woodland (~AD 900-1150) period mortuary site of Schroeder Mounds (Henderson County, Illinois). In order to better understand the physical activities or hazards of the individuals from this site, thirty-seven adult skeletons preserving at least one essentially complete mid (metatarsals) and hind (tarsals) foot were examined for reactive changes that are consistent with traumatic injury. This data is compared to published reports from other Illinois Late Woodland sites. The study is comprised of 17 females, 14 males, and 6 skeletally unsexable adults. In the Schroeder Mounds sample, there were six cases of foot/ankle pathology (6/37, 13.5%), five of which (3/17, 17.6% females; 2/14, 14.3% males) are diagnostically traumatic injuries (5/37, 13.5%). A sixth case is a likely congenital foreshortening of a metatarsal (brachymetatarsia). There is no significant difference between the sexes in the frequency of ankle/foot trauma (p=1.000, Fisher’s test). However, given the small sample size, the results are tentative. The trauma pattern of the Schroeder mounds cases consists of the clinically infrequent tarsometatarsal (Lisfranc joint complex) high-energy misstep injuries, a vertical jump/fall (Pilon fracture), and stress (“march”) fractures of the metatarsal shafts. These injuries are consistent with a highly active and/or mobile community where trauma hazards are arguably equally experienced by both adult males and females.
Keywords: Adults; Late Woodland Period; Schroeder Mounds; Foot; Ankle; Trauma